Pelatihan Mewarnai Teknik Gradasi Untuk Meningkatkan Kreatifitas Guru Di Tks Sirojut Tholibin Palengaan Pamekasan - Aminullah (BAHRI: Jurnal Pengabdian Kepada Masyarakat, 2025)
Early Childhood Education (PAUD) teachers have an important role in creating a fun learning atmosphere and stimulating children's cognitive and affective development. One of the skills that PAUD teachers still lack is the ability to create aesthetic and creative learning media, especially in the field of fine arts. This article discusses the results of Community Service (PKM) activities in the form of color gradation technique training aimed at improving the creativity of Sirojut Tholibin Palengaan Pamekasan Kindergarten teachers. The training method uses an experiential learning approach with three stages: preparation, implementation, and evaluation. The results of the training showed a significant increase in the understanding of the concept of gradation, the technical ability of teachers in applying color techniques, and the emergence of collaborative initiatives between teachers in creating art-based teaching media. The main findings indicate that aesthetic experience contributes to increasing teachers' self-confidence and self-expression in the learning process. This article contributes to the field of educational psychology, especially in the realm of teacher professionalism development through an art-based approach. The conclusion of this activity emphasizes the importance of direct practice-based training to enrich the competence of creative teachers and shows that fine arts can be an effective reflective medium in PAUD learning. These results are important because they can be used as a basis for developing a sustainable training model that integrates aesthetic, psychological, and pedagogical aspects in a balanced manner.